Question #6274

Hi could you help me to understand how I can simplify: 2(4x^2+7x)-(x+2)(8x-2)
Thank you

Expert's answer

& First let's open the braces:

2(4x^2+7x)-(x+2)(8x-2)=8x^2+14x-(8x^2-2x+16x-4)=8x^2+14x-8x^2-14x+4=4 so& no further actions are required, we got single number

Remember, when you open the braces before which there is "-" sign you should change the sigh of every term inside the braces when opening them.

2(4x^2+7x)-(x+2)(8x-2)=8x^2+14x-(8x^2-2x+16x-4)=8x^2+14x-8x^2-14x+4=4 so& no further actions are required, we got single number

Remember, when you open the braces before which there is "-" sign you should change the sigh of every term inside the braces when opening them.

## Comments

## Leave a comment